GAMBARAN KESEJAHTERAAN SPIRITUAL USHER DEWASA MADYA DI GEREJA X JAKARTA - Graciella Faren; Raja Oloan Tumanggor (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Tarumanagara, 2021)
Well-being is something that most people look for. Not only about material, well-being is essentially an achievement of harmony in life from physical, intellectual, social, mental, and also spiritual aspects. Likewise, spirituality becomes one of the supports of individuals to carry out life. Spiritual well-being is important in the lives of middle-aged individuals who have experienced many changes in their lives. These changes have a certain impact on the lives of middle-aged individuals, where middle-aged individuals will evaluate themselves more and live a better quality. This study aims to determine the description of the spiritual well-being of church servants “Church X” in Jakarta. Spiritual well-being is not only focused on the person and God, but other dimensions are related to one another. The research method used is a mixed method that combines questionnaires and interviews. The subjects of this study are the church servants in “Church X” Jakarta, amounting to 33 servants who distributed questionnaires and 3 servants to be interviewed. From the results of the study, it can be concluded that the picture of spiritual well- being of church-servants in Church X is said to be high and has positive well-being from every dimension, personal, communal, environmental and, transcendental. Kesejahteraan adalah sesuatu yang dicari oleh kebanyakan orang. Tidak hanya materi, kesejahteraan pada hakikatnya merupakan pencapaian keharmonisan dalam hidup baik dari aspek fisik, intelektual, sosial, mental maupun spiritual. Demikian pula spiritualitas menjadi salah satu penunjang individu dalam menjalani kehidupan. Kesejahteraan spiritual penting dalam kehidupan individu paruh baya yang telah mengalami banyak perubahan dalam hidup mereka. Perubahan ini memiliki dampak tertentu pada kehidupan individu paruh baya, di mana individu paruh baya akan lebih mengevaluasi diri dan menjalani kualitas yang lebih baik. Penelitian ini bertujuan untuk mengetahui gambaran kesejahteraan spiritual pelayan gereja di Jakarta. Kesejahteraan spiritual tidak hanya terfokus pada pribadi dan Tuhan, tetapi dimensi lain terkait satu dengan yang lainnya. Metode penelitian yang digunakan adalah metode campuran yang menggabungkan kuesioner dan wawancara. Subjek penelitian ini adalah abdi gereja di “Gereja X” Jakarta yang berjumlah 33 orang dengan menyebarkan kuesioner dan 3 orang untuk diwawancarai. Dari hasil penelitian dapat disimpulkan bahwa gambaran kesejahteraan spiritual hamba-hamba Gereja di Gereja X dikatakan tinggi dan memiliki kesejahteraan yang positif dari setiap dimensi baik personal, komunal, lingkungan dan transendental.